Firms` Participation in Tax Amnesty Program Engaged in Financial Reporting Manipulation: An Empirical Evidence from Listed Companies in Indonesia - Gatot Soepriyanto; Yanto Indra; Olivia The; Arfian Zudana (The Winners, 2019)
The research investigated the relation between firms participated in tax amnesty programs and their tendency to manipulate financial statements. The research explored some unique research settings during Indonesia’s tax amnesty period in 2016-2017. To examine the association, the researchers employed Beneish’s M-Score model to categorize the firm’s tendency to manipulate its financial statements. As the test variable, it classified the firm’s participation in the tax amnesty program with a dummy variable, 1 if the firm participated, and 0 otherwise. To control the variations in financial statements manipulation, it also included firm size, leverage, and profitability in our empirical model. Based on the sample of 796 firm-year observations in the Indonesian Stock Exchange (IDX) from the 2012-2017 period, it is found some evidence that firms participate in tax amnesty programs do not engage in financial statements manipulation. Further analysis of the corporate tax avoidance measures shows that those firms do not engage in tax avoidance activities either. The results suggest that firms participate in the tax amnesty programs are not necessary ‘bad firms’, and they just participate as a ‘symbolic’ gesture to get some indirect benefits of the program.